A New Approach in a Gray-Level Image Contrast Enhancement by using Fuzzy Logic Technique - Hussain K., Khaleaf; Kamarul Hawari, Ghazali; Mithaq Na'ma, Raheema; Abdalla, Ahmed N. (IJSRSET, 2015)
Fuzzy Logic technique represents a new approach for gray level image contrast enhancement. The image contrast problem is one of the main problems that confront the researchers in the field of digital image processing, such as in the biomedical image processing like X-Ray and MRI image segmentation for disease classification. In this paper, presenting a new approach to enhancing the image contrast by using fuzzy logic algorithm, so based on the fuzzy rule, we present a new membership equation, which represents the variable threshold level. The proposed method we named it (Fuzzy Hyperbolic Threshold). By using Matlab was implemented the algorithm, and applied to difference gray level images such as old documents images, biomedical images, most of them gives very good results especially with the biomedical images, because of its significant impact on the adjustment of lighting in dark images, clarify its edges, clarify their features and improved image quality.